Effect of Foliar Application of Various Nitrogen Forms on Starch Accumulation and Grain Filling of Wheat (Triticum aestivum L.) Under Drought Stress - Lv, Xiaokang; Ding, Yunpeng; Long, Mei; Liang, Wenxin; Gu, Xiaoyan; Liu, Yang; Wen, Xiaoxia (Frontiers in Plant Science, 2021)
Foliar nitrogen (N) fertilizer application at later stages of wheat (Triticum aestivum L.) growth is an effective method of attenuating drought stress and improving grain filling. The influences or modes of action of foliar application of various nitrogen forms on wheat growth and grain filling need further research. The objective of this study was to examine the regulatory effects of various forms of foliar nitrogen (NO3-, NH4+, and CO(NH2)2) on wheat grain filling under drought stress and to elucidate their underlying mechanisms. The relative effects of each nitrogen source differed in promoting grain filling. Foliar NH4+-N application notably prolonged the grain filling period. In contrast, foliar application of CO(NH2)2 and NO3--N accelerated the grain filling rate and regulated levels of abscisic acid (ABA), z-riboside (ZR) and ethylene (ETH) in wheat grains. Analysis of gene expression revealed that CO(NH2)2 and NO3--N upregulated the genes involved in the sucrose-starch conversion pathway, promoting the remobilization of carbohydrates and starch synthesis in the grains. Besides, activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) were increased whereas the content of malondialdehyde (MDA) declined under foliar nitrogen application (especially NH4+-N). Under drought stress, enhancement of carbohydrate remobilization and sink strength became key factors in grain filling and the relative differences in the effects of three N forms became more evident. In conclusion, NH4+-N application improved the antioxidant enzyme system and delayed photoassimilate transportation. On the other hand, foliar applications of NO3--N and CO(NH2)2 enhanced sink capacity and alleviated drought stress injury in wheat.